A phase I/II, double‐blind, placebo‐controlled study assessing safety and efficacy of C1 esterase inhibitor for prevention of delayed graft function in deceased donor kidney transplant recipients. Issue 12 (14th May 2018) - Jordan, Stanley C.; Choi, Jua; Aubert, Olivier; Haas, Mark; Loupy, Alexandre; Huang, Edmund; Peng, Alice; Kim, Irene; Louie, Sabrina; Ammerman, Noriko; Najjar, Reiad; Puliyanda, Dechu; et al.
Abstract : Delayed graft function (DGF) is defined as need for dialysis early posttransplant. DGF is related to ischemia–reperfusion injury (IRI) that diminishes allograft function and may be complement dependent. Here, we investigate the ability of C1 esterase inhibitor (C1INH) to prevent IRI/DGF in kidney transplant recipients. Seventy patients receiving deceased donor kidney transplants at risk for DGF were randomized to receive C1INH 50 U/kg (#35) or placebo (#35) intraoperatively and at 24 hours. The primary end point was need for hemodialysis during the first week posttransplant. Assessments of glomerular filtration rate and dialysis dependence were accomplished. Complications and safety of therapy were recorded. Similar characteristics with no significant differences in cold‐ischemia time or risk factors for DGF were seen. C1INH did not result in reduction of dialysis sessions at 1 week posttransplant, but significantly fewer dialysis sessions ( P = .0232) were required 2 to 4 weeks posttransplant. Patients at highest risk for DGF (Kidney Donor Profile Index ≥85) benefited most from C1INH therapy. Significantly better renal function was seen at 1 year in C1INH patients ( P = .006). No significant adverse events were noted with C1INH. Although the primary end point was not met, significant reductions in need for dialysis and improvements in long‐term allograft function were seen with C1INH treatment. Abstract : In a placebo‐controlled study for prevention of delayed graft function in kidney allografts, C1 esterase inhibitor demonstrates a significant benefit in improving renal function compared to placebo.